A chemically modified graphene oxide wrapped porous hematite nano-architecture as a high rate lithium-ion battery anode material. Issue 86 (31st August 2016) - Subramaniyam, Chandrasekar M.; Islam, Md. Monirul; Akhter, Taslima; Cardillo, Dean; Konstantinov, Konstantin; Liu, Hua Kun; Dou, Shi Xue
Abstract : Chemically modified graphene oxide wrapped porous hematite nanorods: an interconnected hollow network for excellent lithium storage in lithium ion batteries. Abstract : Successful fabrication of nanoporous metal oxides with carbonaceous nanomaterials can enhance the conductivity of electrodes as well as advance their electrochemical activity to overcome the stress induced during continuous charge–discharge cycling, and this is an effective way to harness their excellent reversible theoretical capacity. Nanoporous hematite (α-Fe2 O3 ) nanorods have been prepared through an advanced spray precipitation method and nanofabricated with reduced graphene oxide (rGO) sheets by simply mixing solutions. This approach helps to introduce a continuous conductive network in between the nanorods to enhance ion interactions, giving the composite a promising electrochemical response as a negative electrode for the lithium-ion battery (LIB). The nanocomposites delivered an outstanding reversible capacity of 1330 mA h g −1 at 100 mA g −1 for 100 cycles and showed excellent rate retention during cycling at different current densities over long cycle numbers, highlighting the potential of this material with its specially designed nano-architecture as an anode material for high energy LIBs for electric vehicles. Along with the overwhelming electrochemical performance of chemically modified graphene-oxide-wrapped hematite porous nanorods (α-Fe2 O3 /rGO), the abundance of the hematite source, and the advanced and environmentally friendly synthesis approach show the potential for large-scale preparation of such electrode materials for real world application.